Beliefs, Agency and Identity in Foreign Language Learning and Teaching - Kalaja, Paula; Barcelos, Ana Maria F.; Aro, Mari.; Ruohotie-Lyhty, Maria; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores the phenomena of believing (or giving personal meanings), acting, and identifying (or identity construction), and the interconnectedness of these phenomena in the learning and teaching of English and other foreign languages.
Keywords: Language and languages-Study and; Psycholinguistics; Applied linguistics